Osteonecrosis of the jaw in a patient under treatment of osteoporosis with oral bisphosphonate - Marília A. Figueiredo; Frederico Buhatem Medeiros; Karem López Ortega (University of São Paulo, 2021)
Although uncommon in patients under oral therapy, bisphosphonate-related osteonecrosis of the jaw (BRONJ) can be a very severe issue. Early intervention with surgical resection should be the preferable method of treating any stage of the disease, resulting in better outcomes and decreasing the morbidity of this condition. A 77-year-old female patient attended the Special Care Dentistry Centre of the University of São Paulo Faculty of Dentistry (CAPE FOUSP) complaining mainly of "an exposed bone that appeared after tooth extraction performed six months earlier". The patient was diagnosed with osteonecrosis associated with bisphosphonate (sodium ibandronate) and surgically treated with removal of bone sequestration and antibiotic therapy. The patient was followed up for six years (a total of 6 appointments), presenting good general health and no sign of bone exposure. Imaging findings showed no changes related to BRONJ either.